The importance of deposit insurance credibility - Bonfim, Diana; Santos, João A.C. (Journal of Banking & Finance, 2023)
Sovereigns usually back up their deposit insurance arrangements to lend them credibility. When the sovereign is in distress, the credibility of deposit insurance might be threatened, with detrimental effects to financial stability. We investigate the behavior of depositors during the euro area sovereign debt crisis to understand the importance of deposit insurance credibility. We find that depositors responded to foreign banks’ decision to convert their subsidiaries into branches. By relocating their deposits into these newly formed branches during a period of sovereign distress, depositors became insured by a deposit insurance scheme with a stronger fiscal backstop. These results document a novel channel through which sovereign-bank links can be reinforced during a crisis: the credibility of deposit insurance.